Assessing barriers to providing tobacco use disorder treatment in community mental health settings with a revised version of the Smoking Knowledge, Attitudes, and Practices (S-KAP) instrument. (March 2021) - Siegel, Scott D.; Laurenceau, J.P.; Hill, Naja; Bauer, Anna-Marika; Flitter, Alex; Ziedonis, Douglas; Stevens, Nathaniel; Hosie Quinn, Mackenzie; Leone, Frank; Beidas, Rinad; Kimberly, John; Schnoll, Robert A.
Highlights: Tobacco use disorder rates are elevated among people with serious mental illness. Rates of tobacco use treatment in mental health settings are low. Organizational interventions that improve training and emphasize a commitment to addressing TUD may improve treatment rates. Abstract: Background: Tobacco use disorder (TUD) rates are 2–3 times higher among people with serious mental illness (SMI) than the general population. Clinicians working in outpatient community mental health clinics are well positioned to provide TUD treatment to this group, but rates of treatment provision are very low. Understanding factors associated with the provision of TUD treatment by mental health clinicians is a priority. Methods: This study used baseline data from an ongoing cluster-randomized clinical trial evaluating two approaches to training clinicians to increase TUD treatment. Following a psychometric assessment of our assessment tool, the Smoking Knowledge, Attitudes, and Practices (S-KAP) instrument, a new factor structure was evaluated utilizing confirmatory factor analysis. Structural equation modeling was then used to examine the associations between TUD treatment practices and clinician, setting, and patient characteristics in a sample of 182 mental health clinicians across 10 mental health clinics. Results: Clinician but not setting or patient characteristics emerged as significant correlates of providing TUD treatment. Specifically, clinicians' general ethical commitment to providing TUD services and perceptions of their skills in providing this type of care were associated with providing TUD treatment. In contrast, clinician perceptions of patient motivation, anticipated quit rates, or available setting resources were not significantly associated with providing TUD treatment. Conclusions: Enhancing community mental health clinician TUD treatment skills and commitment to providing such services may reduce TUD rates among people with SMI. Future studies should evaluate interventions that target these factors.